Associations of Nutritional Status and Soil-Transmitted Helminth Infection with Anemia Among Vegetable Farmers in Gowa District, South Sulawesi - Habibi, Habibi; Fasya Faisal, Nurul; Syarfaini, Syarfaini; Mohamad Nor, Nadeeya 'Ayn Umaisara (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2026)
Introduction:  Anemia is a major public health concern that may reduce health, well-being, and work productivity. Vegetable farmers are potentially vulnerable to anemia because of nutritional inadequacy and frequent occupational exposure to soil, which may increase the risk of Soil-Transmitted Helminth (STH) infection. This study aimed to examine the associations of nutritional status and STH infection with anemia among vegetable farmers in Kanreapia Village, Gowa District, Indonesia. Methods:  This cross-sectional study involved 90 vegetable farmers selected proportionally from a population of 1,437 farmers. Nutritional status was assessed using body mass index (BMI), STH infection was identified through stool examination using the Kato–Katz technique, and hemoglobin concentration was measured using a portable hemoglobin meter. Anemia was classified using sex-specific hemoglobin thresholds. Associations between the study variables and anemia were assessed using appropriate exact tests, with statistical significance defined as p < 0.05. Results:  Among the 90 participants, 21 (23.3%) had anemia, 6 (6.7%) tested positive for STH infection, and 14 (15.6%) were underweight. No statistically significant association was observed between STH infection and anemia (p = 1.000). However, the small number of STH-positive participants limited the statistical power to detect a potentially meaningful association. Nutritional status was significantly associated with anemia (p = 0.016). Conclusion: Nutritional status was significantly associated with anemia among vegetable farmers. In contrast, the evidence regarding the association between STH infection and anemia remains inconclusive because of the small number of infected participants and limited statistical power. Nutritional assessment and anemia screening should be integrated into occupational health programs for agricultural workers, while preventive measures against STH infection should remain part of comprehensive health promotion strategies.